Moringa Oleifera Leave: Hydro-Alcoholic Extract and Effects on Growth Performance of Broilers - Teteh , A.; Lawson, E.; Tona, K.; Decuypere, E.; Gbeassor, M. (International Journal of Poultry Science, 2013)
After the ban in 2006 of the use of antibiotic growth promoter, the search of an alternative led to the utilization of plants like Moringa oleifera Lam. Leaves of this plant are known to have an important component of macronutrients (protein, energy, amino acids), of micronutrients (vitamins, minerals...) and of anti-nutritive factors such as polysaccharides, tannins, saponins, phytates etc. In the aim to give more knowledge about it, leaves are collected from Akoumapé (Vo district in Togo), dried, pulverized and soaked in ethanol-water (50/50). The mixing obtained is homogenized, filtered and evaporated to obtain hydro alcoholic extract. This extract was used to determine its contents in some chemical groups such as total phenols (4.2%), tannin (2.38%), total flavonoids (0.2%) and polysaccharides (21.1%). In addition, a total of 615 day-old broilers (Ross) were divided at random into 3 groups (M0, M1 and M2) fed, respectively with diet 1 (0%), diet 2 (1%) and diet 3 (2%). During the assay, witch lasted for 4 weeks, 15 chicks of each group were slaughtered weekly to collect and weight liver, pancreas, spleen, bursa and thymus. At the same moment, body weight, feed intake, body weight gain and feed conversion ratio were determined. At 28th day, chicks of groups M1 and M2 grew better and have better feed conversion than chicks of groups M0. The same trend is followed by relative organ weights. It can be concluded that Moringa oleifera leaves incorporated at 1 and 2% in feed can improve growth and the lack of significant difference between 1 and 2% could be attributed to the high content of diet 3 in anti-nutrients especially saponins that impair the digestion and absorption of nutrients especially lipids.